Investigation of Some Gaseous and Trace Metal Emissions With Their Emission Factors From Various Brands of Mosquito Coils Used in Nigeria - Francis B Elehinafe; Oyetunji B Okedere; Temitayo E Oladimeji; Sarah O Anabui (SAGE Publishing, 2022)
Mosquito coils of various brands are frequently burnt in indoor environments to drive away mosquitoes-the vector for malaria parasite in regions where the disease is endemic. Emissions from the coils could be a source of indoor air pollution. In this study, various brands of mosquito coils obtained from retail shops in Lagos, Nigeria were burnt in an environmental test box with a view to characterizing carbon monoxide (CO), nitric oxide (NO), and nitrogen dioxide (NO 2 ) in the gaseous emissions as well as elemental concentrations of the ash. Emission characterization achieved with the RAS1700 bio-gas analyzer while AAS was adopted for elemental analysis of the mosquito coil ashes. The emission factor of CO, NO and NO 2 from the coil samples ranged between 0.00138 to 0.26277 μg/m 3 , 0.0002 to 0.00454 μg/m 3 , and 0.000074 to 0.00714 μg/m 3 , respectively. These values were found to be lower than permissible indoor levels recommended by NIOSH. The range of concentrations of Pb, Zn, Cd, Cr, Cu, As, Hg, Fe in the coil ashes from all the brands were 0.02 to 0.04 mg/g, 0.011 to 0.02 mg/g, 0.001 to 0.003 mg/g, 0.004 to 0.008 mg/g, 0.004 to 0.006 mg/g, 0.0001 to 0.0004 mg/g, 0.001 to 0.003 mg/g, and 0.124 to 0.14 mg/g, respectively. Although, the concentrations of the pollutants obtained in this study are within the recommended limits, prolong exposure could trigger chronic disease conditions. Adequate ventilation of indoor environments or utilization of mosquito nets in place of coils could be considered.